Construction and validation of an educational video on foot reflexology - Natiele Favarão da Silva; Natália Chantal Magalhães da Silva; Vanessa dos Santos Ribeiro; Denise Hollanda Iunes; Emília Campos de Carvalho (Universidade Federal de Goias, 2017)
The aim of this study was to construct and validate an educational video about foot reflexology. A methodological study was conducted at a higher education institution in southeastern Brazil, where the video pre-production, production and post-production stages were performed, followed by an evaluation of content understanding and comprehensiveness. The duration of the final version of the educational video is 12'7" (12 minutes and 7 seconds). The experts considered it an educational resource that presents the theme in a clear and objective way. The students considered it a proper educational material and showed good acceptance. The stages adopted for video construction and validation produced a clear, objective and proper educational material. Further studies should evaluate the impact of an educational video on the construction of foot reflexology knowledge.